A Study of the Relationship Between the ACT College Mathematics Readiness Standard and College Mathematics Achievement. (June 2016) - Harwell, Michael; Moreno, Mario; Post, Thomas
This study examined the relationship between the American College Testing (ACT) college mathematics readiness standard and college mathematics achievement using a sample of students who met or exceeded the minimum 3 years high school mathematics coursework recommended by ACT. According to ACT, a student who scores 22 or higher on the ACT mathematics test has a relatively high probability of earning a passing grade in his or her first college mathematics course. Data from 11, 324 students who attended 1 of 27 four-year postsecondary institutions in the upper Midwest were used to study this relationship. Overall, there was evidence that meeting the mathematics readiness standard was related to college mathematics achievement for students who completed at least 3 years of high school mathematics. The results have important implications for school district staff advising college-intending students on mathematics course-taking, college admissions staff evaluating student readiness for college-level mathematics, and researchers studying college readiness.